OPTIMASI SUHU ANNEALING UNTUK EMPAT PRIMER RAPD PADA KACANG HIJAU (Vigna radiata L.) - Herman Herman; Martupa Nainggolan; Dewi Indriyani Roslim (UIR Press, 2018)
Determination of annealing temperature of the primer is the first step for genetic diversity analysis using molecular markers such as RAPD (Random Amplified Polymorphic DNA). This study aims to determine annealing temperature (Ta) of RAPD primers on Kampar Mungbean. Methods included total DNA extraction, electrophoresis, and annealing temperature optimization of four RAPD markers namely OPD-20, OPI-06, OPI-13, dan OPX-13. Optimization was conducted by reducing the Tm value (Time melting) of each primer with 3 (Tm-3) and 5 (Tm-5). The results showed that the optimization using OPD-20 and OPX-13 produced bands at Tm-3 and Tm-5. Meanwhile, optimization using OPI-06 and OPI-13 resulted in bands at Tm-3. The next step was to choose the exact Ta based on the clear and bright band. In conclusion, exact Ta for OPD-20, OPI-06, OPI-13, and OPX-13 were 36,1°C, 38,1°C, 35,4°C, and 32,5°C respectively.